Factors contributing to illiteracy among males in Wilson's Run All Age School - Smith, Stephanie Ophelia (My University, 2006)
It is a well-known fact that most boys who drop out of school are likely to have weak or poorly developed literacy skills. These dropouts become vulnerable to a life of underemployment, unemployment and for worse, are at higher risk of becoming criminal offenders. There is some evidence that boys and girls may learn different orientations to school work and to learning and in this respect are influenced differently by the mother and the father (Connell et al., 1982). Addressing issues posed by the literacy gap has become more urgent than ever before, especially in developing countries like Jamaica, where social conditions, such as poverty can jeopardize children’s well-being. These social conditions can make the challenge of bringing these affected children to a high level of literacy seem overwhelming. It is known however, that engaged readers have a much greater chance of staying in school, expanding career and life options, and maturing into self-actualized adults (Brozo, 2002). This study will consider factors that contribute to the high illiteracy rate in the Wilson’s Run All Age School in Trelawny, Jamaica. The community is located high in the Cockpit Country of Trelawny. It is a secluded, tight-knit community, where everybody is familiar and are all related. It is a small farming community, where the farmers cultivate mainly yams on small plots of land. The women of the district are also mostly farmers or stay-at-home moms or if employed are mainly domestic helpers. The community members enjoy a very simplistic
This file was last viewed in Adobe Reader 7.0
Keywords: Literacy -- Jamaica -- Trelawny, Parish of; Schoolboys -- Jamaica -- Trelawny, Parish of